Time Management of High School Students Viewed from Gender in Pandemic (Departement of Psychology, Faculty of Education, Universitas Negeri Semarang, 2023)
The pandemic period resulted in changes to the learning activity system and required students to be able to adapt to these conditions, one of which was how they managed their time in the midst of their busyness in the scope of education when the pandemic was still ongoing. Men and women have different characteristics that can affect their attitudes and behavior. This study aims to determine whether there are differences in the time management of high school students in terms of gender during the pandemic. The approach used is quantitative with a comparative design to see the differences. The data collection tool uses the TMBS (Time Management Behavior Scale) scale. The population in this study were students of SMA Negeri 3 Semarang with an age range of 15-18 years. The number of samples collected was 163 subjects with stratified random sampling technique. The data analysis method consisted of normality test, homogeneity test, and hypothesis testing with the independent sample T-Test. The results of the analysis showed that there was no significant difference in the time management of high school students in terms of gender. Overall time management of SMA Negeri 3 Semarang students are in the medium category. In the aspect of setting goals and priorities, in general, male students are higher than female students. In the aspect of planning and scheduling mechanisms and the aspect of preference for being organized, in general, female students are higher than male students.